2017
DOI: 10.5935/abc.20170167
|View full text |Cite
|
Sign up to set email alerts
|

Left Atrial Appendage Closure with Amplatzer Cardiac Plug in Nonvalvular Atrial Fibrillation: Safety and Long-Term Outcome

Abstract: BackgroundAtrial fibrillation (AF) is a cardiac arrhythmia with high risk for thromboembolic events, specially stroke.ObjectiveTo assess the safety of left atrial appendage closure (LAAC) with the Amplatzer Cardiac Plug for the prevention of thromboembolic events in patients with nonvalvular AF.MethodsThis study included 15 patients with nonvalvular AF referred for LAAC, 6 older than 75 years (mean age, 69.4 ± 9.3 years; 60% of the male sex).ResultsThe mean CHADS2 score was 3.4 ± 0.1, and mean CHA2DS2VASc , 4.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 25 publications
1
3
0
Order By: Relevance
“…17 We did not observe DRT in our patients with TEE imaging at the 1 st , 6 th , and 12 th month after LAA occlusion, corroborating their results. 17 There is some controversy among studies regarding thrombus formation over the device. The individualized antiplatelet treatment may explain this difference in our patient series.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…17 We did not observe DRT in our patients with TEE imaging at the 1 st , 6 th , and 12 th month after LAA occlusion, corroborating their results. 17 There is some controversy among studies regarding thrombus formation over the device. The individualized antiplatelet treatment may explain this difference in our patient series.…”
Section: Discussionsupporting
confidence: 90%
“…Interestingly, DAPT at discharge was associated with a lower risk of thrombus, and only 23.2% of the study group was discharged with this treatment. Costa et al 17 published patient outcomes over a 12-month follow-up and found no DRT. 17 We did not observe DRT in our patients with TEE imaging at the 1 st , 6 th , and 12 th month after LAA occlusion, corroborating their results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the second registry, Marcio Costa et al, 13 evaluated 15 patients with nonvalvular AF and high risk of bleeding, submitted to implantation of the ACP prosthesis. In this small series, the procedure was successfully performed in all cases with no reports of hemopericardium or prosthesis displacement.…”
Section: Referencesmentioning
confidence: 99%